ZQL: A Compiler for Privacy-Preserving Data Processing - Fournet, Cédric; Kohlweiss, Markulf (Proceedings of the 22th USENIX Security Symposium, USA, August 14-16, 2013, 2013)
ZQL is a query language for expressing simple computations on private data. Its compiler produces code to certify data, perform client-side computations, and verify the correctness of their results. Under the hood, it synthesizes zero-knowledge protocols that guarantee both integrity of the query results and privacy for all other data. We present the ZQL language, its compilation scheme down to concrete cryptography, and the security guarantees it provides. We report on a prototype compiler that produces F# and C++. We evaluate its performance on queries for smart-meter billing, for pay-as-you-drive insurance policies, and for location-based services.